2009
DOI: 10.4137/cin.s3229
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Carcinogens by Hepatic Transcript Profiling in Rats following 28-day Administration

Abstract: This study aimed at discriminating carcinogens on the basis of hepatic transcript profiling in the rats administrated with a variety of carcinogens and non-carcinogens. We conducted 28-day toxicity tests in male F344 rats with 47 carcinogens and 26 non-carcinogens, and then investigated periodically the hepatic gene expression profiles using custom microarrays. By hierarchical cluster analysis based on significantly altered genes, carcinogens were clustered into three major groups (Group 1 to 3). The formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Anesthesia is used for pain control and is necessary in toxicological studies, and several anesthesia methods are employed in the fields of toxicogenomics, for example CO 2 -O 2 anesthesia (Matsumoto et al, 2009(Matsumoto et al, , 2014. Currently, isoflurane anesthesia is becoming widely used for this purpose (Nagate et al, 2007;Edmands et al, 2013;Nakazato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia is used for pain control and is necessary in toxicological studies, and several anesthesia methods are employed in the fields of toxicogenomics, for example CO 2 -O 2 anesthesia (Matsumoto et al, 2009(Matsumoto et al, , 2014. Currently, isoflurane anesthesia is becoming widely used for this purpose (Nagate et al, 2007;Edmands et al, 2013;Nakazato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We performed a cluster analysis of the gene expression profile for rat liver in a 28-day repeated dose toxicity study using 73 chemicals consisting of 47 carcinogens and 26 non-carcinogens and identified three major carcinogen groups, each with a characteristic gene expression profile (Matsumoto et al, 2009). These results indicate that there are three kinds of characteristic gene sets that show gene expression changes specifically for each of three groups of carcinogens; therefore, the prediction of carcinogens based on characteristic gene sets should be performed individually for each group.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 51 chemicals, including 29 for trainingphase trials and 22 for validation-phase trials, were selected from among the chemicals used in previous studies (Matsumoto et al, 2009(Matsumoto et al, , 2014. The names of the chemicals and their toxicological profiles are shown in Table 1 and Table 2.…”
Section: Chemicalsmentioning
confidence: 99%
“…After applying the log2 ratio data of 15 predictive genes to CARCINOscreen ® , the largest value among the predictive scores obtained using the three prediction formulae was determined as the final predictive score. The details of the microarray experiments for CARCINOscreen ® are described in Matsumoto et al (2009Matsumoto et al ( , 2011Matsumoto et al ( and 2014.…”
Section: Rna Extractionmentioning
confidence: 99%
See 1 more Smart Citation